Applications of Geo-Textiles for the stabilization of soil: A Review - Saurabh Kumar (PREPARE@u® | IEI Conferences, 2021)
Soil serves as a support for the construction and effectively distributes load. If the soil is unable to bear load effectively, the structure fails in a variety of ways, including settlement, fractures, and other types of structural collapse. If soil is not properly stable, it sometimes creates a lot of problems for construction engineers, mainly due to the low bearing capacity of soil and its high compressibility. Therefore, to enhance the engineering properties and load bearing capacity of subsoil (known as Soil Stabilization), a wide range of methods and reinforcing materials are available, such as: geo-textile sheets, geo-grid, metal strips, bar mats, etc. The strength and stability of soil mass can be improved and increased with the help of the stabilization process, and the settlement of structures built on it is reduced. Geo-textile (Geo-synthetic) is a reinforcing material made of thin permeable sheets of synthetic fibres that are widely used in modern engineering practice to strengthen foundations, slopes, crushed stone columns, road pavements, etc. From the various studies done by many researchers in recent years, it is determined that the geo-textile used in all the projects or research work has a significant impact on the properties of the soil. In this paper, before and after putting in the geo-textile, shear strength, dry density, permeability, and CBR values have been compared, and an effort has been made to collect information about soil stabilization using geo-textiles, which includes a brief summary of their procedure and their applications and identifies the different areas that need further attention or improvement.